Model validity of randomised placebo-controlled trials of non-individualised homeopathic treatment. Issue 4 (November 2017) - Mathie, Robert T.; Van Wassenhoven, Michel; Rutten, A.L.B.; Klein-Laansma, Christien T.; Eizayaga, José; Pla i Castellsagué, Anna; Jong, Miek C.; Manchanda, Raj K.; Dantas, Flávio; Oberbaum, Menachem; Frye, Joyce; Roniger, Helmut; et al.
Abstract : Background: The comprehensive systematic review of randomised placebo-controlled trials (RCTs) in homeopathy requires examination of a study's model validity of homeopathic treatment (MVHT) as well as its risk of bias (extent of reliable evidence). Objective: To appraise MVHT in those RCTs of non-individualised homeopathy that an associated investigation had judged as 'not at high risk of bias'. Design: Systematic review. Methods: An assessment of MVHT was ascribed to each of 26 eligible RCTs. Another 49 RCTs were ineligible due to their high risk of bias. Main outcome measures: MVHT and the prior risk of bias rating per trial were merged to obtain a single overall quality designation ('high', 'moderate', 'low'), based on the GRADE principle of downgrading. Results: The trials were rated as 'acceptable MVHT' (N = 9), 'uncertain MVHT' (N = 10) and 'inadequate MVHT' (N = 7); and, previously, as 'reliable evidence' (N = 3) and 'non-reliable evidence' (N = 23). The 26 trials were designated overall as: 'high quality' (N = 1); 'moderate quality' (N = 18); 'low quality' (N = 7). Conclusion: Of the 26 RCTs of non-individualised homeopathy that were judged 'not at high risk of bias', nine have been rated 'acceptable MVHT'. One of those nine studies was designated 'high quality' overall ('acceptable MVHT' and 'reliable evidence'), and is thus currently the only reported RCT that represents best therapeutic practice as well as unbiased evidence in non-individualised homeopathy. As well as minimising risk of bias, new RCTs in this area must aim to maximise MVHT and clarity of reporting. Highlights: The study appraised model validity of homeopathic treatment (MVHT). The sample comprised 26 randomised controlled trials (RCTs) of non-individualised homeopathy that were 'not at high risk of bias'. MVHT and risk of bias rating per trial were merged to obtain a single overall quality designation ('high', 'moderate', 'low'). The 26 trials were designated overall as: 'high quality' (N = 1); 'moderate quality' (N = 18); 'low quality' (N = 7). Only one study was designated 'high quality' overall ('acceptable MVHT' and 'reliable evidence').